2014
DOI: 10.1364/boe.5.001812
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic responses in rat brain during transcranial direct current stimulation: a functional near-infrared spectroscopy study

Abstract: In the present study, we monitored hemodynamic responses in rat brains during transcranial direct current stimulation (tDCS) using functional near-infrared spectroscopy (fNIRS). Seven rats received transcranial anodal stimulation with 200 μA direct current (DC) on their right barrel cortex for 10 min. The concentration changes of oxygenated hemoglobin (oxy-Hb) were continuously monitored during stimulation (10 min) and after stimulation (20 min). The trend of hemodynamic response changes was modeled using line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 32 publications
0
30
0
2
Order By: Relevance
“…45 While not involving a form of epilepsy, a study that used NIRS to monitor the hemodynamics responses in rat brains during transcranial direct current stimulation found that the HbO concentration increased almost linearly during this stimulation. 46 In a study of patients with periodic limb movements during sleep, the cerebral hemodynamics varied among the different sleep stages, and there were also changes in the phase differences between HbO and HbR during the different sleep stages in normal controls. 47 The present study has demonstrated the presence of cerebral hemodynamics disturbances in restless leg syndrome patients with periodic limb movements in sleep and suggests that NIRS can be used to determine the cerebral blood flow.…”
Section: Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…45 While not involving a form of epilepsy, a study that used NIRS to monitor the hemodynamics responses in rat brains during transcranial direct current stimulation found that the HbO concentration increased almost linearly during this stimulation. 46 In a study of patients with periodic limb movements during sleep, the cerebral hemodynamics varied among the different sleep stages, and there were also changes in the phase differences between HbO and HbR during the different sleep stages in normal controls. 47 The present study has demonstrated the presence of cerebral hemodynamics disturbances in restless leg syndrome patients with periodic limb movements in sleep and suggests that NIRS can be used to determine the cerebral blood flow.…”
Section: Epilepsymentioning
confidence: 99%
“…46 In a study of patients with periodic limb movements during sleep, the cerebral hemodynamics varied among the different sleep stages, and there were also changes in the phase differences between HbO and HbR during the different sleep stages in normal controls. 47 The present study has demonstrated the presence of cerebral hemodynamics disturbances in restless leg syndrome patients with periodic limb movements in sleep and suggests that NIRS can be used to determine the cerebral blood flow.…”
mentioning
confidence: 99%
“…Відомо, що астроцити відіграють важливу роль у регулюванні мозкового кровообігу [7]. Беручи до уваги тісний взаємозв'язок активності нейронів і мозкового кровообігу, очікується, що ТМП має впливати на гемодинаміку, збільшуючи перфузію мозку [8,9]. ТМП може бути використана як окремий терапевтичний метод, так і в поєднанні зі стандартною терапією для коригування збудливості кори головного мозку і покращення рухової активності у пацієнтів із різними неврологічними розладами [10].…”
Section: вступunclassified
“…Fifteen minutes of anodal tDCS at 100 μA increased CBF up to 30 min afterwards, whereas 100 μA of cathodal tDCS decreased CBF by 25% for up to 30 min. Similarly, a functional near-infrared spectroscopy (fNIRS) study on rats also observed an increase in oxygenated hemoglobin during anodal tDCS, which persisted for 30 min afterwards [50]. Whether these physiological effects are a direct result of electric fields (e.g., vessel dilation effects from DC fields- [51,52]) or secondary effects from polarized neurons affecting other cell functions and cascades remains an open question.…”
Section: Animal Modelsmentioning
confidence: 99%